2019
DOI: 10.1002/cplu.201900448
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Fluorimetric Turn‐Off Detection of Copper(II) by Two Different Mechanisms in Calix[4]arene‐Based Chemosensors and Chemodosimeters

Abstract: Isoxazolo‐pyrene tethered calix[4]arenes selectively detect copper(II) ions without interference from related perchlorate ions. The fluorescence emission of the probes, synthesised by nitrile oxide alkyne cycloaddition, and characterised by spectroscopic and crystallographic data, is rapidly reduced by Cu(II) ions. Detection limits are in the micromolar or sub‐micromolar range (0.3–3.6 μM) based on a 1 : 1 sensor:analyte interaction. Voltammetric behaviour and 1H NMR data provide new insights into the sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It is worth mentioning that in several previous works using calix [4]arene-based ionophores, particularly those relying in dansyl groups [49] sensitivities for Cu(II) and Pb(II) are of the same order of magnitude, whereas for Hg(II) the affinity was in general even higher, overall making the attained selectivity for Cu(II) in these systems rather poor. In other works [50], a good selectivity was achieved for Cu(II) in comparison, for instance, with Pb(II) or Hg(II), although in a lower sensitivity when compared to polymer 5.…”
Section: Inclusion Complexes and Sensing Of Metal Cationsmentioning
confidence: 75%
See 1 more Smart Citation
“…It is worth mentioning that in several previous works using calix [4]arene-based ionophores, particularly those relying in dansyl groups [49] sensitivities for Cu(II) and Pb(II) are of the same order of magnitude, whereas for Hg(II) the affinity was in general even higher, overall making the attained selectivity for Cu(II) in these systems rather poor. In other works [50], a good selectivity was achieved for Cu(II) in comparison, for instance, with Pb(II) or Hg(II), although in a lower sensitivity when compared to polymer 5.…”
Section: Inclusion Complexes and Sensing Of Metal Cationsmentioning
confidence: 75%
“…For non-polymeric probes, a calix [4]arene containing two pyrenyl amine groups showed a K sv of 1.49 × 10 4 M −1 [48], while a series of calixarene receptors with appended dansyl groups display association constants ranging from 1.45 × 10 3 − 6.31 × 10 4 M −1 [49]. Pyrenyl-isoxazolo-tethered calix [4]arenes also display significant responses to Cu(II) with K a in the range 6.00 × 10 3 − 4.71 × 10 4 M −1 [50]. When considering conjugated polymers, either fluorene-alt-phenylene and phenyleneethynylene-alt-thienyleneethynylene type polymers, containing attached, respectively, N-cyclohexyl carbamates (K sv = 1.10 × 10 4 M −1 ) [51] and tolylterpyridyl (K sv = 2.01 × 10 5 M −1 ) [52] groups as recognition elements, have been used for Cu(II) detection.…”
Section: Inclusion Complexes and Sensing Of Metal Cationsmentioning
confidence: 99%
“…While some sensing systems do not involve counterion participation, there is precedence for an anion dependence on cation sensing across a range of mechanisms. 35 It is suggested that anion effects can be due to their pH 40 and in another case, the Cu 2+ detection by means of oxidation behavior toward a ferrocene unit is reported to be profoundly influenced by the counterion. 41 The apparent difference between the lower-rim propyl substituted 2 (no-response in UV/vis or fluorescence) and the unsubstituted analogue 1 (∼88% fluorescence quenching) to 10 equivalents of Cu(ClO 4 ) 2 can be understood by considering the sensing mechanism shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…24 Recently, Heaney and co-workers also reported the synthesis of p-t-butylcalix [4]arene with lower-rim 1,3-bisisoxazolylpyrene units showing high selectivity toward Cu 2+ ions in CH 3 CN with fluorescence turn-off. 34,35 However, there has been no report on the synthesis of lower-rim isoxazole-functionalized calix [4]arenes with both chromogenic and fluorogenic properties for Cu 2+ sensing.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies were conducted in the solution phase. [17][18][19][20][21] Recently, research using chemosensing materials mixed with polymer-based solid supports was initiated due to an anticipated enhanced stability, the convenience of on-site analysis, easily usable platforms, ease of disposal and reversibility. [22][23][24][25][26][27][28][29] Practically, the solid nanomaterial capacity for adsorbing metal ions can establish the sensitivity and selectivity of the probes.…”
mentioning
confidence: 99%